Self-perceived risk for diabetes among non-diabetic adolescents with overweight/obesity: Findings from NHANES - Twarog, John P. (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• Explores perceived diabetes risk among US adolescents with overweight/obesity. • Significant racial differences were found in the perception of risk for diabetes. • Effective healthcare communication may lower the risk of developing diabetes.